2019
DOI: 10.1186/s12886-019-1054-9
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function relationships in glaucoma using enhanced depth imaging optical coherence tomography-derived parameters: a cross-sectional observational study

Abstract: Background To investigate structural and functional correlations in glaucoma patients using enhanced depth imaging spectral-domain optical coherence tomography (EDI OCT)-derived parameters. Methods We prospectively enrolled healthy participants and glaucomatous patients with a wide range of disease stages. All participants underwent visual field (VF) testing (SITA - Standard 24–2; Carl Zeiss Meditec, Dublin, CA) and EDI OCT imaging (Spectralis; Heidelberg Engineering Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 45 publications
4
26
1
Order By: Relevance
“…Previous studies have revealed that the structure-function relationship is better with the BMO-MRW parameter than other conventional OCT-based and CSLO-based parameters [15,35,36]. Pollet-Villard et al [15] have demonstrated that the structure-function relationship is significantly greater with BMO-MRW than other optic disc OCT parameters including neuro-retinal rim thickness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that the structure-function relationship is better with the BMO-MRW parameter than other conventional OCT-based and CSLO-based parameters [15,35,36]. Pollet-Villard et al [15] have demonstrated that the structure-function relationship is significantly greater with BMO-MRW than other optic disc OCT parameters including neuro-retinal rim thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the structure-function relationship in lamina cribrosa (LC)-derived parameters has been inspected. Lopes et al [36] have found that BMO-MRW has better structure-function correlations than LC-derived parameters including prelaminar neural tissue thickness and area, anterior LC depth, and LC thickness and area. These findings partly support our study results that most (86.1%) included subjects showing normal classification of BMO-MRW and abnormal classification of RNFL demonstrated normal findings on VF tests.…”
Section: Discussionmentioning
confidence: 99%
“…We adopted the same glaucoma definition that we used in our previously published studies [16, 17]. In short, characteristic glaucomatous optic neuropathy was defined as a vertical cup-to-disc ratio (VCDR) ≥0.6, asymmetry of VCDR ≥0.2 between eyes, presence of localized or diffuse pRNFL defects and/or neuroretinal rim defects in the absence of any other abnormalities, which could explain such findings [16, 18, 19].…”
Section: Methodsmentioning
confidence: 99%
“…When it comes to using ONH parameters for glaucoma diagnosis and monitoring (besides the well-established BMO-MRW analysis), more recently, researchers have been investigating new metrics based both on prelaminar neural tissue (PLNT) and laminar analyses [14-16]. In previous studies from our group in this research line [17], we reported on glaucoma-related features within the ONH and on structure-function relationships in glaucoma (considering both laminar and prelaminar parameters) using EDI OCT quantitative analysis. Even though some interesting data about these new EDI OCT-based parameters have been emerging, their usefulness as an additional tool for glaucoma diagnosis is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It has been lately shown that BMO-MRW provides better performance in the diagnosis of glaucoma than traditional NRR parameters [ 8 , 9 , 10 ]. BMO-MRW also shows a better structure-function relationship in glaucoma than other pre-existing peripapillary RNFL and parameters of confocal scanning laser ophthalmoscope [ 10 , 11 , 12 , 13 ]. We have previously described a disagreement between BMO-MRW and RNFL in classification analysis of color-codes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%